PERBEDAAN HASIL BAKTERI TAHAN ASAM METODE ZIEHL NEELLSEN DAN TES CEPAT MOLEKULER (TCM) DENGAN LAMA PENYIMPANAN 48 JAM - Aristoteles; Yuliana Maya Sari; Denny Juraijin (IKesT Muhammadiyah Palembang, 2024)
Background: Tuberculosis (TBC) is an infectious disease caused by Mycobacterium tuberculosis, a dorect human-to-human infectious disease not caused by witchcraft or curses TB germ most often attack the lungs but can also attack other organs such as the lymph nodes, bones, brain, skin and others. The diagnosis of pulmonary TB is established based on the clinical picture, physical examination, radiological picture, laboratory examination and tuberculin test. The diagnosis of pulmonary tuberculosis currently used routinely in labpratories including hospitals and health centers is a bacteriological diagnosis using acid-fast bacillus microscopic techniques (BTA) and molecular rapid test (TCM). TCM examination is a molecular detection methode based on nested real-time PCR. The use of TCM is a priority for TB examination because it has several advantages, including: High sensitivity, fast and results can be known in approximately 2 hours. Objectives: To determine differences in the results of acid-fast bacteria Ziehl Neelsen method and the molecular rapid test (TCM) with a storage time of 48 hours. Method: This type of research is pure experiment. The research was conducted in the Celikah Health Center laboratory in February 2023 with a total sample of 5 smear samples (+1). Result: The results showed that there was no difference in the tesults of acid-fast bacteria between the ziehl neelsen method and the molecular rapid test (TCM) for 48 hours of storage. The wilcoxon test results obtained a value of p = 0,157. Conclusion: The molecular rapid test method has better sensitivity and specificity in the diagnosis of tuberculosis thab microscopic examination using ziehl neelsen staining.